Validity And Reliability Of Mars-10 Questionnaire On Antipsychotic Adherence In Schizophrenia Patients - Nailis Syifa; Irsan Fahmi Almuhtarihan; Erika Zahrotul Avia Habba; Uhai’atun Nisa’ Nazliza; Jaza Faizun Nadifa (Universitas Muhammadiyah Malang, 2024)
Non-adherence in schizophrenia treatment is still a major problem in the successful treatment of schizophrenia. MARS-10 (Medication Adherence Report Scale-10) questionnaire is a self-reported questionnaire to measure patient’s adherence which has been implemented in some disease. However, there is still no study investigated the application of MARS-10 into schizophrenia patients in Indonesia. The purpose of this study was to determine the reliability and validity of the MARS-10 questionnaire in schizophrenia cases in Indonesia. This design of this study was a prospective, descriptive quantitative analysis approach with a cross-sectional design. Thirty schizophrenia patients from Saiful Anwar Hospital Malang, Lawang Mental Hospital, and UMM Hospital were used as research samples. Determining the validity of the questionnaire using the Pearson Product Moment correlation test, the correlation coefficient value r count is greater than the r table value, which is 0.361. In determining the reliability of the questionnaire, an analysis was carried out using the Cronbach's Alpha coefficient which showed the Cronbach's Alpha coefficient of 0.742. The results of the validity and reliability tests show that the MARS-10 questionnaire that has been translated into Indonesian is valid and reliable for measuring the level of compliance of schizophrenia patients with antipsychotic treatment in Indonesia.